2011
DOI: 10.1055/s-0031-1296767
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of a Fluid Extract Combination of Thyme Herb and Ivy Leaves and Matched Placebo in Adults Suffering from Acute Bronchitis with Productive Cough

Abstract: Oral treatment of acute bronchitis with thyme-ivy combination for about 11 days was superior to pla-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1
19

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(111 citation statements)
references
References 7 publications
5
86
1
19
Order By: Relevance
“…The validation of the used parameter BSS is based on several studies on acute bronchitis [21,22,25,33,34]. The baseline BSS in our study was comparable to the severity of illness as reflected in the baseline BSS from other interventional studies [22,25,26,34]. Therefore, we assume that the patients who participated in our study constitute a representative sample of the patient collective suffering from acute bronchitis; thus the external validity of our study can be deduced.…”
Section: Ear and Labyrinth Disordersmentioning
confidence: 72%
See 2 more Smart Citations
“…The validation of the used parameter BSS is based on several studies on acute bronchitis [21,22,25,33,34]. The baseline BSS in our study was comparable to the severity of illness as reflected in the baseline BSS from other interventional studies [22,25,26,34]. Therefore, we assume that the patients who participated in our study constitute a representative sample of the patient collective suffering from acute bronchitis; thus the external validity of our study can be deduced.…”
Section: Ear and Labyrinth Disordersmentioning
confidence: 72%
“…Several clinical studies showed improved symptom relief in adults suffering from acute bronchitis with plant preparations containing 1,8-cineole and/or linalool when compared to placebo [20][21][22][23][24][25][26]. Spike lavender essential oil (Spicae aetheroleum, Spicae ae.)…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22][23][24][25][26][27][28][29] Recently, a review of all trials employing the BSS until April 2012 was published. 30 Moreover, Kardos and colleagues reported of the BSS as a current example for the use of a composite scale.…”
Section: Clinical Psychometric Measures For Acute Bronchitismentioning
confidence: 99%
“…Finally, the BSS was brought to the notice of the international scientific community by over a dozen publications [13][14][15][16][17][19][20][21][22][23][24][25][26][27][28][29]34 and it was not rejected. All these arguments speak for a high content validity of the BSS.…”
Section: Content Validitymentioning
confidence: 99%